Роль Санкт-Петербургской академии художеств в развитии современнего монгольского изобразительного искусства - О, Сосор (Journal of International Studies, 2007)
English title: Role of the St. Petersburg's Academy of Fine Arts in the development of contemporary Mongolian Arts